2023
DOI: 10.1111/jtxs.12741
|View full text |Cite
|
Sign up to set email alerts
|

Emerging nondestructive techniques to quantify the textural properties of food: A state‐of‐art review

Abstract: Texture is an important sensory attribute that drives consumer acceptance of any food material. In recent times consumers' demand for high‐quality food urges food industries to provide food with consistent textural properties. However, texture measurement not just requires a trained sensory panel but also a considerable amount of time and effort. On the flip side, human observation could be subjective hence repeatability of the result may not be ensured and/or relied on. Contrary to that, objective methods for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 218 publications
(243 reference statements)
0
3
0
Order By: Relevance
“…At Day 3, firmness and toughness were reduced by 68.2% and 44.4%, respectively, when compared to those found on Day 0 (Table 1). Firmness or hardness can be defined as resistance shown by the meat towards destruction (Mishra et al ., 2023). The toughness or chewiness is defined as the energy used for mastication of the product or continuous energy is required for the destruction of the meat.…”
Section: Resultsmentioning
confidence: 99%
“…At Day 3, firmness and toughness were reduced by 68.2% and 44.4%, respectively, when compared to those found on Day 0 (Table 1). Firmness or hardness can be defined as resistance shown by the meat towards destruction (Mishra et al ., 2023). The toughness or chewiness is defined as the energy used for mastication of the product or continuous energy is required for the destruction of the meat.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, chewiness indicates the internal structural strength, showing the energy required to disrupt food structure. These textural parameters were usually affected by the moisture content of foods and the aggregation strength between molecules (Gayatri et al., 2023; Zhao et al., 2023). Combined with the results shown in Figure 1a, LRE might reduce the hardness and chewiness by increasing moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Barroso and others [ 60 ] reported differing results obtained from instrumental tissue assessments of salmon muscle, which could be explained by significant differences between individual parts of the fish and sampling point selections. Strength is most commonly used to measure textural quality and to predict the mechanical variation of tissue [ 61 ]. However, the results showed that this parameter only distinguishes the tail from the abdomen and back, and the difference between the abdomen and the back was insignificant.…”
Section: Resultsmentioning
confidence: 99%